Helicobacter pylori infection presenting as childhood recurrent headache: A case report - Shivalingaiah, Madhura; Kariyappa, Mallesh; Hanumanna, Anil Kumar; Yelsangikar, Kalpana Ramesh (Indian Journal of Child Health, 2019)
Headache in children and adolescents is common and there is a steady increase in the incidences in recent years. Migraine has been attributed as the most common cause of recurrent headache under the age of 6 years. Migraine is reported in 3.9% of children aged 7–15 years which increases from 1.7% in 7 years old to 5.3% in 15 years old. Many studies have focussed on the association between headache and Helicobacter pylori infection which is acquired early in the childhood beyond the age of 10 years through fecal-oral route transmission. Here, we report a case of H. pylori infection in a 13-year-old female child who presented with a history of recurrent headache refractory to standard treatment. Later, the child was diagnosed to have H. pylori gastritis. Headache responded to 4 weeks course of H. pylori eradication therapy.